Saccharomyces cerevisiae derived postbiotic alters gut microbiome metabolism in the human distal colon resulting in immunomodulatory potential in vitro - Duysburgh, Cindy; Miclotte, Lisa; Green, Justin B.; Watts, Kevin T.; Sardi, Maria I.; Chakrabarti, Anirikh; Khafipour, Ehsan; Marzorati, Massimo (Frontiers in Microbiology, 2024)
The yeast-based postbiotic EpiCor is a well-studied formulation, consisting of a complex mixture of bioactive molecules. In clinical studies, EpiCor postbiotic has been shown to reduce intestinal symptoms in a constipated population and support mucosal defence in healthy subjects. Antiinflammatory potential and butyrogenic properties have been reported in vitro, suggesting a possible link between EpiCor's gut modulatory activity and immunomodulation. The current study used a standardized in vitro gut model, the Simulator of the Human Intestinal Microbial Ecosystem (SHIME ® ), to obtain a deeper understanding on host-microbiome interactions and potential microbiome modulation following repeated EpiCor administration. It was observed that EpiCor induced a functional shift in carbohydrate fermentation patterns in the proximal colon environment.Epicor promoted an increased abundance of Bifidobacterium in both the proximal and distal colon, affecting overall microbial community structure. Co-occurrence network analysis at the phylum level provided additional evidence of changes in the functional properties of microbial community promoted by EpiCor, increasing positive associations between Actinobacteria with microbes belonging to the Firmicutes phylum. These results, together with a significant increase in butyrate production provide additional support of EpiCor benefits to gut health. Investigation of hostmicrobiome interactions confirmed the immunomodulatory potential of the applied test product. Specific microbial alterations were observed in the distal colon, with metabotyping indicating that specific metabolic pathways, such as bile acid and tryptophan metabolism, were affected following EpiCor supplementation. These results, especially considering many effects were seen distally, further strengthen the position of EpiCor as a postbiotic with health promoting functionality in the gut, which could be further assessed in vivo.